STRATEGI PENGEMBANGAN SISTEM PENDIDIKAN AKUNTANSI DALAM UPAYA MENANGGAPI PERSAINGAN MASYARAKAT EKONOMI ASEAN DENGAN MENGGUNAKAN ANALISIS SWOT - Ririn Breliastiti; Elfina Astrella Sambuaga (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2017)
Opening opportunities through the ASEAN Community as well as two inseparable sides of the coin, which provides wide job opportunities, as well as higher competition. The accountant is one of the many professions allowed in the MEA. Based on the latest data from the Ministry of Research, Technology and Higher Education, the total Accounting Study Program in Indonesia amounted to 1,322, for all levels (forlap.ristekdikti.go.id/prodi). This is a challenge for the world of education to be able to create graduates who qualified and have international competitiveness. To support this, the world of education should have a committed management and high quality education, thus supporting the atmosphere in the learning process. As part of the realization of ASEAN's vision in 2020, the ASEAN Community (ASEAN Community) is expected to improve the development of human resources through quality education, skills and training (ASEAN Secretariat, 2008). According to Jitpaisanwattana et al. (2015), a combination of key components in management education including curicula, contents, activities, desired workforce qualification, evaluation. Therefore, the urgency of this research is to provide strategies that can be applied in the development of accounting education in facing the ASEAN Economic Community (MEA) based on the components of curicula, contents, activities, and desired workforce qualification, using SWOT analysis. The methods to be conducted in this study include the collection of secondary data and methods of observation of educational institutions, as well as experiments, FGC and interviews with accounting students follow Samsudin et al. (2015). The conclusions that can be drawn from this research are; (2) the existence of a rigid education system becomes the weakness of accounting education institutions in Indonesia, (3) the competence of accounting students in facing the opportunity of free competition it can not be said enough, (4) students are expected to be more independent in addressing personal problems, and seeking accurate information related to the needs of the world of work.